Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis